Mapping Islamic finance and new technologies: research and managerial perspectives - Calandra, Davide; Marseglia, Roberto; Vaccaro, Vincenzo; Chmet, Federico (European Journal of Islamic Finance, 2022)
New technologies promote radical changes in how banking services are delivered. The field of Islamic finance is not exempt from radical changes and is gaining increasing attention from academics and practitioners. Although several scientific studies have been conducted on the impact of technologies on specific Islamic finance instruments, no research has examined bibliometric variables in this area. This study aims to cover this gap by conducting a bibliometric and open coding analysis on 170 sources of published studies on Islamic finance and technology. Our study detects the most influential authors, journals and countries of publication that currently prioritise research in this field. In addition, the thematic analysis reveals that among the niche themes are applications of technology to Takaful. Among the motor themes is the opportunity for technology to facilitate decision-making in Islamic banks. Finally, in terms of originality, this study highlights the field's current state by combining methodological approaches and providing valuable insights for future research. Moreover, it is also a starting point for practitioners to fully understand the characteristics and potential of technology in Islamic finance. Finally, the article provides researchers with a research agenda to guide future research ideas.